2016
DOI: 10.5588/ijtld.15.0872
|View full text |Cite
|
Sign up to set email alerts
|

<I>M. tuberculosis</I> DNA detection in nasopharyngeal mucosa can precede tuberculosis development in contacts

Abstract: The detection of M. tuberculosis DNA in the nasopharyngeal mucosa of contacts is an infrequent event that in this instance preceded the development of pulmonary TB. Its pathogenic role requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many of these 59 studies did not have the primary aim of assessing diagnostic accuracy. Many recorded few cases of active TB (often < 10) 22,[25][26][27][29][30][31][32][33][35][36][37][38]40,[42][43][44][45]47,48,50,51,[56][57][58][59][62][63][64][65][67][68][69][70][71][72][73][74][75]77,78 and/or were restricted to groups such as patients infected with HIV, 9,28,29,36,49,51,56,60,65,…”
Section: Diagnostic Performance Of Interferon Gamma Release Assays Fomentioning
confidence: 99%
“…Many of these 59 studies did not have the primary aim of assessing diagnostic accuracy. Many recorded few cases of active TB (often < 10) 22,[25][26][27][29][30][31][32][33][35][36][37][38]40,[42][43][44][45]47,48,50,51,[56][57][58][59][62][63][64][65][67][68][69][70][71][72][73][74][75]77,78 and/or were restricted to groups such as patients infected with HIV, 9,28,29,36,49,51,56,60,65,…”
Section: Diagnostic Performance Of Interferon Gamma Release Assays Fomentioning
confidence: 99%
“…Nonetheless, the findings observed in microbiota diversity in contacts who were about to acquire the infection remain to be confirmed in a larger cohort. Previous work by our group and others has reported that transient Mtb localization in the upper respiratory tract mucosa can rarely occur after exposure to a PTB case 19 , 20 . However, the persistence, replication and direct effect of Mtb in nasopharyngeal mucosa is unlikely, as we did not detect Mtb in the nasopharyngeal samples.…”
Section: Discussionmentioning
confidence: 69%
“…From included manuscripts (appendix pp 26-33 for study characteristics; appendix p 5 includes full methodological details and results by study), we classified types of upper respiratory tract sampling into four groups: laryngeal swabs (32 studies ), nasopharyngeal aspirate (ten studies [43][44][45][46][47][48][49][50][51][52] ), oral swabs (18 studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] ), and other (mouthwash three studies, [71][72][73] nasal swabs one study, 74 saliva four studies, [75][76][77][78] and other mucosa or dental samples three studies [79][80][81] ). Studies were published between May 13, 1933, and Dec 19, 2022, from South Africa (11 studies), Norway (seven studies), UK (seven studies), Peru (four studies), Uganda (seven studies), Canada (three studies), India (three studies), USA (three studies), Australia (two studies), Germany (two studies), Kenya (two studies), and one study from each of Brazil, Chile, China, Slovakia and Czech Republic, Denmark, Finland, France, Hungary, Italy, Japan, Malawi, Moldova, Mozambique, South Korea, southeast Asia (individual countries not specified), Spain, Sweden, Taiwan, Turkey, and Yemen.…”
Section: Resultsmentioning
confidence: 99%